Multimodal Investigation of Neuronal Responses - Pakenham, Daisie Olivia (2021)
This thesis describes an investigation of neuronal responses with both magnetoencephalography (MEG) and functional magnetic resonance imaging (fMRI). MEG and fMRI are widely used in neuroscience. However, aspects of the MEG and fMRI signal are still not well understood, particularly post-stimulus responses – responses which occur after a stimulus has ended. Post-stimulus responses have been shown to correlate with various illnesses and as a result, MEG and fMRI have yet to reach their full potential clinically.